Schistosomal Lipids Activate Human Eosinophils via Toll-Like Receptor 2 and PGD2 Receptors: 15-LO Role in Cytokine Secretion - Magalhães, Kelly G.; Luna-Gomes, Tatiana; Mesquita-Santos, Fabio; Corrêa, Rafael; Assunção, Leonardo Santos; Atella, Georgia Correa; Weller, Peter F.; Bandeira-Melo, Christianne; Bozza, Patricia T. (Frontiers in Immunology, 2019)
Parasite-derived lipids may play important roles in host-pathogen interactions and immune evasion mechanisms. Remarkable accumulation of eosinophils is a characteristic feature of inflammation associated with parasitic disease, especially caused by helminthes. Infiltrating eosinophils are implicated in the pathogenesis of helminth infection by virtue of their capacity to release an array of tissue-damaging and immunoregulatory mediators. However, the mechanisms involved in the activation of human eosinophils by parasite-derived molecules are not clear. Here we investigated the effects and mechanisms of schistosomal lipids-induced activation of human eosinophils. Our results showed that stimulation of human eosinophils in vitro with total lipid extracts from adult worms of S. mansoni induced direct activation of human eosinophils, eliciting lipid droplet biogenesis, synthesis of leukotriene (LT) C4 and eoxin (EX) C4 (14,15 LTC4) and secretion of eosinophil pre-formed TGFβ. We demonstrated that main eosinophil activating components within S. mansoni lipid extract are schistosomal-derived lysophosphatidylcholine (LPC) and prostaglandin (PG)D2. Moreover, TLR2 is up-regulated in human eosinophils upon stimulation with schistosomal lipids and pre-treatment with anti-TLR2 inhibited both schistosomal lipids- and LPC-, but not PGD2-, induced lipid droplet biogenesis and EXC4 synthesis within eosinophils, indicating that TLR2 mediates LPC-driven human eosinophil activation. By employing PGD2 receptor antagonists, we demonstrated that DP1 receptors are also involved in various parameters of human eosinophil activation induced by schistosomal lipids, but not by schistosomal LPC. In addition, schistosomal lipids and their active components PGD2 and LPC, triggered 15-LO dependent production of EXC4 and secretion of TGFβ. Taken together, our results showed that schistosomal lipids contain at least two components—LPC and PGD2—that are capable of direct activation of human eosinophils acting on distinct eosinophil-expressed receptors, noticeably TLR2 as well as DP1, trigger human eosinophil activation characterized by production/secretion of pro-inflammatory and immunoregulatory mediators.